Optimizing Public Policy Evaluation Using Data and Evidence-Based Approaches for Sunan Kuning Semarang, Indonesia Closure - Isnaeni Yuliani; Amrizarois Ismail; Ainun Nazriah; Robe'ah Yusuf (Journal of Governance and Public Policy)
Since the closure of the Sunan Kuning (Argorejo) localization area in Semarang in 2019, a range of secondary issues have emerged, including not only morality concerns but also impacts on economic cycles, public health, and social structures. The closure, part of a national initiative to eliminate prostitution, aimed to address moral and health concerns but unintentionally led to challenges such as the displacement of sex workers and the shift of prostitution to online platforms. This study aims to evaluate the policy surrounding closure using Robert E. Stake’s Countenance Model (1967), which includes three stages: (1) antecedent, (2) transactions, and (3) outcomes. A qualitative approach was adopted, with purposive sampling to select stakeholders for Delphi interviews, supplemented by a literature review. Data analysis followed an interactive model comprising data reduction, data display, and conclusion drawing and verification. These processes were conducted simultaneously to enable structured and focused data collection. The findings indicated that the policy has not been optimally implemented. Key recommendations include the necessity of strong political will by the government in every stage of the policy process and the importance of incorporating insights from prior research and past policy experiences. The study’s main contribution lies in developing innovative strategies for the systematic involvement of stakeholders, ensuring that public policy is both data-driven and responsive to the real-world challenges affected communities face. This research offers a novel framework for integrating qualitative policy evaluation with participatory stakeholder engagement in post-localization contexts.